Child sexual abuse prevention involving mothers: A Quasi‐experimental study with Protection Motivation Theory‐based intervention. Issue 8 (23rd April 2022) - Bhagyalakshmi, K. C.; Kumar, Aneesh
Abstract: Child sexual abuse (CSA) is a worldwide problem. The safety of children is everybody's responsibility. Parental and family involvement is crucial in the CSA prevention process. Parental lack of knowledge may increase the risk of abuse among children. Educating parents is crucial as children are mostly dependent on them. The role of mothers in educating children on CSA is of relevance as they are identified as more sensitive and responsible caregivers. The present study aimed to promote knowledge and attitude towards CSA prevention among mothers through a psychoeducation program. A pre‐ and posttest design ( n  = 67) was used with an intervention based on Protection Motivation Theory (PMT). A CSA knowledge and attitude scale was developed for the assessment of the participants for the study. There were significant changes in knowledge and attitude among the participants after the intervention. The prevention of CSA will be effective with knowledge gains after the PMT‐based intervention. The intervention programs that involve mothers in CSA education have benefits. The findings of this study can be helpful to incorporate public health approaches to devise evidence‐based parental programs in community settings.